2019
DOI: 10.1111/jcpt.13085
|View full text |Cite
|
Sign up to set email alerts
|

Target‐controlled infusion of dexmedetomidine effect‐site concentration for sedation in patients undergoing spinal anaesthesia

Abstract: What is known and objective Dexmedetomidine has been a preferred sedative for patients undergoing regional anaesthesia and is mostly administered via conventional zero‐order infusion. Recently, a pharmacokinetic‐pharmacodynamic (PKPD) model of dexmedetomidine has been published, but no external validation has been reported in clinical trials. We aimed to administer target‐controlled infusion (TCI) of dexmedetomidine at the effect‐site concentration (Ce) to patients undergoing spinal anaesthesia and investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
2
8
0
1
Order By: Relevance
“…In the current study, we targeted patients who were undergoing surgery under spinal anesthesia and were treated with dexmedetomidine, which was administered as described in the pharmacopeia (a popular method). A significant correlation between the BIS value and MOAA/S score was observed, as reported in previous studies [16][17][18][19][20][21]. However, the average value of the BIS for specific sedation level showed difference.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the current study, we targeted patients who were undergoing surgery under spinal anesthesia and were treated with dexmedetomidine, which was administered as described in the pharmacopeia (a popular method). A significant correlation between the BIS value and MOAA/S score was observed, as reported in previous studies [16][17][18][19][20][21]. However, the average value of the BIS for specific sedation level showed difference.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have evaluated the performance of BIS and its correlations with clinical sedation scales (Richmond agitation-sedation scale, Ramsay sedation scale, and OAA/S) under dexmedetomidine sedation and reported that the performance of the BIS was reliable during dexmedetomidine sedation. However, most of these studies were conducted in ICU patients who were on mechanical ventilation, and one study was conducted in patients undergoing spinal anesthesia with dexmedetomidine sedation using target-controlled infusion, a method not often used in clinical practice because it requires a special infusion pump [16][17][18][19]. In the current study, we targeted patients who were undergoing surgery under spinal anesthesia and were treated with dexmedetomidine, which was administered as described in the pharmacopeia (a popular method).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol (5 mg/kg•h) and remifentanil (0.2 μg/ kg•min) were micropumped to maintain intraoperative general anesthesia, and cisatracurium was given according to the actual situation of the patients. Additional intravenous anesthetics were stopped at 30 min before the end of surgery, and the pumping of dexmedetomidine was stopped before suturing [11][12][13]. e secretions in the catheter and oral cavity were aspirated at the end of the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The pharmacodynamic model is complex and describes four clinical effects: the BIS, the Modified Observer's Assessment of Alertness/Sedation (MOAA/S) score, heart rate and mean arterial pressure. Despite the complexity, use of this model for TCI enables the anaesthetist to titrate the drug to achieve a desired BIS or probability of a certain MOAA/S score [26], whereas the model also provides information about the other effects (magnitude of bradycardia and the likely change in blood pressure from baseline).…”
Section: Pharmacokinetic/ Pharmacodynamic Models In Clinical Practice: Sedationmentioning
confidence: 99%